Catastrophe Bond and Sovereign Debt: Flooding Risk Transfer for Thailand - Wattanakoon , Panit; Suanin , Wanissa (Thailand and The World Economy, 2023)
The dangers posed by natural disasters are a source of concern for policymakers. Severe occurrences caused by the devastation may contribute to the economic collapse and increase in sovereign debt. A catastrophe bond (CAT bond) can be utilized to transfer catastrophe risk to the financial market. This article examines how policymakers can use a CAT bond as an ex-ante financial instrument to raise funding. By using Thailand as a case study, this research replicates the loss caused by floods using three potential catastrophe bond packages based on the coverage size of the simulated loss. We find that all packages can slow the rising trend of the debt-to-GDP ratio under catastrophic flooding. Even if it cannot, on average, reduce the debt-to-GDP ratio, the greatest coverage bond provides the government with the highest level of utility since it can help mitigate the economic collapse during disaster seasons.